2022
DOI: 10.1039/d2fo02577a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism investigation of fermented egg-milk peptides on colonic inflammatory diseases: based on in vivo and in silico research

Abstract: Fermented egg-milk beverage (FEMB) could alleviate the symptom of inflammatory diseases, but the underlying regulating mechanism of effective ingredients is unclear now. Our research was designed to confirm the protective...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…A significant decrease in the abundance of Verrucomicrobia and a significant increase in the abundance of Candidatus saccharimonas in colitis mice after gavage administration of 200 mg/kg of egg white peptides as previous studies reported . Similarly, egg white peptides prepared using microbial fermentation significantly increased the abundance of Lactobacillus in mice with colitis and significantly increased the level of SCFAs. , In addition, the tripeptides, IRW and IQW, identified in ovotransferrin hydrolysate, increased the richness of microbiota, normalized the F/B ratio, and decreased the relative abundance of Helicobacter in the mouse model. , …”
Section: Regulation Of Gut Microbiota By Ewpsupporting
confidence: 75%
See 3 more Smart Citations
“…A significant decrease in the abundance of Verrucomicrobia and a significant increase in the abundance of Candidatus saccharimonas in colitis mice after gavage administration of 200 mg/kg of egg white peptides as previous studies reported . Similarly, egg white peptides prepared using microbial fermentation significantly increased the abundance of Lactobacillus in mice with colitis and significantly increased the level of SCFAs. , In addition, the tripeptides, IRW and IQW, identified in ovotransferrin hydrolysate, increased the richness of microbiota, normalized the F/B ratio, and decreased the relative abundance of Helicobacter in the mouse model. , …”
Section: Regulation Of Gut Microbiota By Ewpsupporting
confidence: 75%
“…86 Similarly, egg white peptides prepared using microbial fermentation significantly increased the abundance of Lactobacillus in mice with colitis and significantly increased the level of SCFAs. 72,87 In addition, the tripeptides, IRW and IQW, identified in ovotransferrin hydrolysate, increased the richness of microbiota, normalized the F/B ratio, and decreased the relative abundance of Helicobacter in the mouse model. 105,127 Animal models and clinical studies have demonstrated the association between ecological dysregulation of the gut microbiota and obesity-related diseases.…”
Section: Regulation Of Gut Microbiota In the Damagedmentioning
confidence: 97%
See 2 more Smart Citations
“…79 Moreover, research conducted by Li et al has demonstrated the synergistic anticancer potential of self-assembling amphiphilic α-la peptides when combined with curcumin. 80 Additionally, the self-assembled egg white peptides have been reported to possess notable antiinflammatory, 81 antioxidant, and wound-healing capabilities. 82 Kamal et al revealed that whey proteins hydrolyzed peptides exhibited potent antimicrobial activity against various pathogenic bacteria, inhibiting their growth and viability.…”
Section: Application Of Fpdmps In Food Processesmentioning
confidence: 99%